2020
DOI: 10.1063/1.5130889
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic titanium nitride via atomic layer deposition: A low-temperature route

Abstract: To integrate plasmonic devices into industry, it is essential to develop scalable and CMOS compatible plasmonic materials. In this work, we report high plasmonic quality titanium nitride (TiN) on c-plane sapphire by plasma enhanced atomic layer deposition (PE-ALD). TiN with low losses and high metallicity was achieved at temperatures below 500°C, by exploring the effects of chemisorption time, substrate temperature and plasma exposure time on material properties. Reduction in chemisorption time mitigates prema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…We note that our TiN films grown on sapphire at low deposition temperatures of ≈450 °C have already been shown to exhibit high optical performance (peak FOM of 2.5) due to our optimized PE‐ALD process involving prolonged plasma exposure and reduced chemisorption times to mitigate precursor decomposition. [ 37 ] In regard to the structural quality, Figure shows the comparison of the X‐ray diffraction (XRD) 2 θ – ω and φ scans of the TiN films on Si (001) with and without the MgO interlayer. The TiN (002) peak in the XRD 2 θ – ω scan along the growth direction is barely apparent for the film grown directly on the Si (001) substrate (Figure 1a), indicating the low crystalline quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that our TiN films grown on sapphire at low deposition temperatures of ≈450 °C have already been shown to exhibit high optical performance (peak FOM of 2.5) due to our optimized PE‐ALD process involving prolonged plasma exposure and reduced chemisorption times to mitigate precursor decomposition. [ 37 ] In regard to the structural quality, Figure shows the comparison of the X‐ray diffraction (XRD) 2 θ – ω and φ scans of the TiN films on Si (001) with and without the MgO interlayer. The TiN (002) peak in the XRD 2 θ – ω scan along the growth direction is barely apparent for the film grown directly on the Si (001) substrate (Figure 1a), indicating the low crystalline quality.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition parameters of a plasma exposure time of 25 s, a chemisorption time of 0.5 s, and a substrate temperature of 450 °C were used based on previous optimization routines to obtain the material with the best optical properties. [ 37 ] For a comparative study, the simultaneous growth of TiN directly on Si (001) without an MgO interlayer, and on bulk MgO (001) substrates was also carried out. The growth rate of the TiN films was about 1.3 Å per cycle, independent of the substrate material.…”
Section: Methodsmentioning
confidence: 99%
“…Fomra et al [ 57 ] have reported high plasmonic quality TiN films grown by PE‐ALD on c ‐plane sapphire. TiN layers with low losses, high metallicity, and a plasma frequency below 500 nm were achieved at substrate temperatures less than 500 °C by optimizing the ALD parameters (chemisorption time, plasma exposure time, and substrate temperature).…”
Section: Tin Thin Filmsmentioning
confidence: 99%
“…The high performance of TiN as a plasmonic material has been recently exploited for variety of applications, including plasmonic waveguides on sapphire, [48] nanohole metasurfaces on sapphire, [49] nanoantennas on sapphire, MgO and Si substrates, [37,50,51] and cancer treatment. [52] High-quality TiN is generally grown via reactive sputtering, [30,37,39,42,53,54] PLD, [43,55] molecular-beam epitaxy (MBE), [38,56] and ALD [41,51,[57][58][59][60][61][62][63][64][65][66][67][68] techniques. Unfortunately, preparation of high-quality TiN usually requires high deposition or postdeposition annealing temperatures that are not compatible with CMOS processes.…”
Section: Tin Thin Filmsmentioning
confidence: 99%
“…Successful implementation of the titanium nitride as a plasmonic component in photonic devices has been demonstrated on the example of hyperbolic metamaterials working in the visible and infrared ranges [9,10], high-temperature-stable and irradiation-resistant broadband absorber [11], nanoantennas, or other nanostructures able to increase optical response [12][13][14][15][16][17], SERS (Surface-Enhanced Raman Spectroscopy spectroscopy) substrate [18], and remote optical temperature sensor [19]. Apart from applications, the current literature addresses issues related to optimizing the plasmonic properties [20][21][22][23][24][25][26] and the stability of the thin films [26][27][28]. Some quite modern reviews are also available [29,30].…”
Section: Introductionmentioning
confidence: 99%